Analysis of the Mechanism for the Development of Allergic Skin Inflammation and the Application for Its Treatment: Keratinocytes in Atopic Dermatitis - Their Pathogenic Involvement - Mayumi Komine (Elsevier, 2009)
Abstract.: Atopic dermatitis frequently accompanies bronchial asthma, allergic rhinitis, and allergic conjunctivitis, the pathogenesis of which has frequently focused on the immunological aspects; however, skin eruption in atopic dermatitis occurs mainly in the epidermis, whose barrier function and cytokine expression have been revealed to be abnormal. In addition, the epidermis contains Langerhans cells, antigen-presenting cells, which could be considered the sentinel of the immune system. Some atopic dermatitis patients have been revealed to have mutations or SNPs (single-nucleotide polymorphisms) in the filaggrin gene, which affect the epidermal barrier function. Proteinases in the epidermis are of importance in maintaining the epidermal barrier, abnormalities of which have been reported in atopic dermatitis. Abnormalities of various cytokines and chemokines produced by keratinocytes have also been reported. Thymic stromal lymphopoietin (TSLP) produced by keratinocytes has recently been a focus in atopic dermatitis. Adrenergic/cholinergic responses in the epidermis could also influence the pathogenesis of atopic dermatitis. Considering epidermal keratinocytes as a trigger of immune abnormalities, not only as a peripheral effector, would be important to further disclose the pathogenesis of this enigmatic disorder. Keywords:: keratinocyte, atopic dermatitis, epidermal barrier, cytokine/chemokine, proteinase, allergic inflammation